Efek Nefroprotektif Nanoemulsi Kulit Jeruk (Citrus Reticularis) dan Aloe Vera: Studi pada Tikus Model Nefropati Diabetik Terinduksi Uninefrektomi dan Streptozotocin - Dede Syifa Izzatul Aulia; Mutia Fudhla Karima; Ridha Syifaa Ar-Rahiim; Evy Sulistyoningrum (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Diabetic nephropathy is a chronic complication resulting from hyperglycemia, which triggers oxidative stress and inflammation, leading to progressive structural and functional kidney damage. Orange peel and Aloe vera contain bioactive compounds with antioxidant and antifibrotic properties that may protect the kidneys from diabetes induced injury. Nanoemulsion delivery systems can enhance the bioavailability of these extracts in the body. This experimental study aimed to analyze the nephroprotective effects of orange peel and Aloe vera nanoemulsion in a diabetic nephropathy rat model, including glomerular morphology and kidney function. A post-test only control group design was used on Wistar rats divided into five groups: positive control, negative control, and three treatment groups receiving varying nanoemulsion doses. Glomerular structure was evaluated by assessing the number of glomeruli exhibiting synechiae and analyzed using the Kruskal–Wallis test due to non-normal data distribution, yielding p=0.2387 (p>0.05), indicating no significant differences among groups. Urea levels were elevated above normal, whereas creatinine levels remained within normal limits. Although not statistically significant, the treatment groups demonstrated nephroprotective tendencies, shown by improvements in glomerular synechiae in the diabetic nephropathy model.